Stereotipype Tokoh Ayah dalam Cerpen Guru Karya Putu Wijaya: Kajian Dekonstruksi Derrida - Sonya Trikandi; Yusro Edy Nugroho; Agus Nuryatin (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2023)
Abstract This research aims to describe stereotype The father figure in the short story Guru by Putu Wijaya is in accordance with Derrida's theory. The research method uses a deconstruction approach to Derrida's theoretical literary works. Deconstruction of literary works is able to analyze short stories from the language that has various meanings in a text. The data in this research is in the form of text documents containing fragments of characters, plot, caritas background in short stories. The data source comes from Jawa Pos, 05/08/2016 edition of teacher's short stories by Putu Wijaya. The data collection technique uses heuristic techniques, namely reading the initial stages by analyzing the elements contained in the story such as characters. The data analysis technique uses the hermeneutic technique of in-depth reading of literary works in the form of the social environment in the story and analyzing it in depth in accordance with deconstruction theory. Research result stereotype The character of the father can be shown based on dialogue or the character's speech, such as the environment, the character's reactions to other characters. It is known that the character of the father does not depict the attitude of a parent who is firm, wise and unemotional. And the meaning of opposition which shows my father's bad thoughts towards teachers is a form of criticism of the government.